If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-1)(x-1)=(2x+1)(x+1)-(x+3)(x+3)
We move all terms to the left:
(x-1)(x-1)-((2x+1)(x+1)-(x+3)(x+3))=0
We multiply parentheses ..
(+x^2-1x-1x+1)-((2x+1)(x+1)-(x+3)(x+3))=0
We calculate terms in parentheses: -((2x+1)(x+1)-(x+3)(x+3)), so:We get rid of parentheses
(2x+1)(x+1)-(x+3)(x+3)
We multiply parentheses ..
(+2x^2+2x+x+1)-(x+3)(x+3)
We get rid of parentheses
2x^2+2x+x-(x+3)(x+3)+1
We multiply parentheses ..
2x^2-(+x^2+3x+3x+9)+2x+x+1
We add all the numbers together, and all the variables
2x^2-(+x^2+3x+3x+9)+3x+1
We get rid of parentheses
2x^2-x^2-3x-3x+3x-9+1
We add all the numbers together, and all the variables
x^2-3x-8
Back to the equation:
-(x^2-3x-8)
x^2-x^2-1x-1x+3x+1+8=0
We add all the numbers together, and all the variables
x+9=0
We move all terms containing x to the left, all other terms to the right
x=-9
| 0.5p+-3.45=-1.2 | | 11/2+t=31/2;t=2 | | 12x-9=4x-15 | | h=169 | | 10=2(4x+3) | | 2/5(1/2y+5)−4/5=1/2y−1+-11/0y | | 36c=1,116 | | (x-1)²=(2x+1)(x+1)-(x+3)² | | 0.8x=12. | | 3/x-1=4/x-1 | | 12+f=29 | | (x-1)^2=(2x+1)*(x+1)-(x+3)^2 | | Y=0.99x+0.96 | | 9/12=x/12 | | 5x+2+3x+6=360 | | 1.8g=-27 | | 5x+2+3x+6=180 | | -24x+4^x=-32 | | (x-1)(x-1)=(2x+1)*(x+1)-(x+3)*(x+3) | | f(-2)(0)=-5^2-20 | | 1^5x+2=243 | | -7/2+2/7u=-8/3 | | (2x–3)=(13x–41)=180 | | (-2)(x)=-5^2-20 | | 3^(2x)=17 | | -6.7=b-2.5 | | 1-6x=3/2x+7 | | −18+5z=37 | | 3.1*x=55.8 | | m-7=-19 | | 0.12x=3.36 | | /115=25y |